Analysis of vibration characteristics of joined cylindrical-spherical shells. (1st September 2020) - He, Qi; Dai, Hong-Liang; Gui, Qin-Feng; Li, Jun-Jian
Graphical abstract: Highlights: Cylindrical shell-spherical shell concatenation structure is investigated. Energy calculation at the interface and boundary is simplified. Influence of structural parameters and loading modes are considered. Abstract: In this paper, the free and forced vibration of joined cylindrical-spherical shells (JCSSs) subjected to classical boundary conditions are investigated by a variational method. A JCSSs is divided into its components (i.e., cylindrical and spherical shells) at the cylinder-sphere junction. The interface continuity and geometric boundary conditions are approximately enforced by means of a modified variational principle and least-squares weighted residual method. Donnell shell theory is used to formulate the theoretical model. Double mixed series are adopted as admissible displacement functions for each shell component. In addition, the forced vibration response of the JCSSs is gained through the Newmark-β method. Through the comparison and analysis study, it is obvious that the proposed method has a good stable and rapid convergence property and the results of this paper closely agreed with those obtained by published literatures and the finite element method. The influence of structural parameters and different loading modes on free and forced vibration characteristics of JCSSs are considered.